An Analysis on Changing Security Policies of Turkey after the July 15th Coup Attempt - Niyazi Karabulut; Önder Kutlu (Otoritas : Jurnal Ilmu Pemerintahan, 2020)
Turkey's security policies have been largely a result of its historical and political experiences. The July 15th (2016) coup attempt indicates a turning point in Turkey's security policies as it has been strategically important in shaping the political, structural, and bureaucratic structure of the country. A number of reasons would be mentioned in this account. The failed attempt reiterated the need for making swift reforms in its institutionalization and capacity-building with regard to security priorities. As a result, Turkey has got to make certain reforms on its security strategies and state structure. Elimination of the members and elements of the Fetullahist Terrorist Organization (FETO) initiating the coup attempt have become the first priority at the list. Secondly, dismissal of the personnel from nearly every state and government agency has been the second measure. Finally, certain reforms have been implemented in re-structuring the state, the army, and security organizations alike. This paper aims to present and eventually interpret the changes on the security policies of Turkey after the July 15th coup attempt; then the policies are analyzed through the reports produced by think tank organizations. Among these, the relevant reports of İstanbul Policy Center (IPC) and SETA are examined in order to analyze possible effects of the changes, and a contingency analysis is done through those reports. The main purpose of the study is to analyze how Turkey changed its security policies and what are the concurrent results of these changes. Having done so, this study purposes to reveal pros and cons of the changes together with pertinent solutions and suggestions. Consequently, the findings of Turkey would have the prospect to draw lessons for other nations and systems to learn.